Griburius leonardii, a new species from French Guiana (Coleoptera: Chrysomelidae: Cryptocephalinae) - Davide Sassi (Natural History Sciences, 2023)
A new species of Griburius Haldeman 1849 is described from French Guiana. In some respects, the new species is similar to Griburius errans (Suffrian 1852), distributed in Mexico, but it differs in the details of the dorsal pattern, the narrower interocular distance, and the size.